2009
DOI: 10.2147/ijn.s7287
|View full text |Cite
|
Sign up to set email alerts
|

Daunorubicin-loaded magnetic nanoparticles of Fe3O4 overcome multidrug resistance and induce apoptosis of K562-n/VCR cells in vivo

Abstract: Multidrug resistance (MDR) is a major obstacle to cancer chemotherapy. We evaluated the effect of daunorubicin (DNR)-loaded magnetic nanoparticles of Fe3O4 (MNPs-Fe3O4) on K562-n/VCR cells in vivo. K562-n and its MDR counterpart K562-n/VCR cell were inoculated into nude mice subcutaneously. The mice were randomly divided into four groups: group A received normal saline, group B received DNR, group C received MNPs-Fe3O4, and group D received DNR-loaded MNPs-Fe3O4. For K562-n/VCR tumor, the weight was markedly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
(46 reference statements)
1
21
0
1
Order By: Relevance
“…It has been previously reported that MNP-Fe 3 O 4 with anticancer drugs could effectively improve efficiency of chemotherapeutic agents which has a synergistic effect in multidrug resistance. 12,13 Our present study demonstrated that the unique MNPsFe 3 O 4 could increase the biological effects and decrease the side effects of ART. MTT results revealed that after being combined with MNPs-Fe 3 O 4 (100:1, M/M), ART showed an enhanced cytotoxic effect on K562 cells; the copolymer of 100 µM ART with 1 µM MNPs-Fe 3 O 4 had the most enhanced cytotoxicity among the five groups.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been previously reported that MNP-Fe 3 O 4 with anticancer drugs could effectively improve efficiency of chemotherapeutic agents which has a synergistic effect in multidrug resistance. 12,13 Our present study demonstrated that the unique MNPsFe 3 O 4 could increase the biological effects and decrease the side effects of ART. MTT results revealed that after being combined with MNPs-Fe 3 O 4 (100:1, M/M), ART showed an enhanced cytotoxic effect on K562 cells; the copolymer of 100 µM ART with 1 µM MNPs-Fe 3 O 4 had the most enhanced cytotoxicity among the five groups.…”
Section: Discussionsupporting
confidence: 53%
“…10,11 We have recently reported that MNPs-Fe 3 O 4 , as an anticancer drug deliverer, could enhance the sensitivity of anticancer drugs and reverse the drug resistance of tumor cells. 12,13 Apoptosis is the main mechanism of cell death, and is mediated by a cell-intrinsic suicide program, with the relative balance of pro-and anti-apoptotic signaling pathways determining the fate of the cell. There are two main pathways in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results are found for the percentage of apoptotic K562 cells induced by DNR-Sol and DNR-MNPs. In a previous study by our group, 33,34 daunorubicin-loaded magnetic nanoparticles of Fe 3 O 4 were more effective than daunorubicin alone in multidrug-resistant cells. Our present synthesis method is different to the previous one, which relied on mechanical absorption and polymerization, resulting in loose linkage of DNR and MNPs.…”
Section: Discussionmentioning
confidence: 82%
“…[26][27][28] For example, DNR-loaded magnetic nanoparticles of Fe 3 O 4 can overcome MDR. 29 In another study, nickel nanoparticles have shown increased cancer cell membrane permeability. 7 However, the use of nanoparticles as DNR sensitizers has been of major concern due to their known toxicity.…”
Section: Discussionmentioning
confidence: 97%